Our experience in laparoscopic surgery - Veirano, Gustavo; Morelli, Raúl; Bermúdez, Jorge (Cirugía del Uruguay, 1992)
The advantage of laparoscopic cholecistectomy as regards decrease of operatory morbility as compared to conventional surgery is object of more literature every day. Ear/ier return to woek, pain decrease and better post-operative comfort as we/1 as reduced hospitalization time are we/1-known advantages of laparoscopic surgery. In this paper the authors present the experience of the British Hospital Surgical Team on the first 79 laparoscopic cholecystectomies. They a/so present their experience on appendicectomy and other surgical procedures where laparoscopy is tending to have good indication. The results of the cholecystectomy series is analysed. Average operating time: 77·_ Mortality: 0%. lntraoperative